Analysis of the distribution of temperature and humidity in different variants of external walls made of hemp-lime composite - Alberska, Anna; Brzyski, Przemysław (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
Proper design of the building component, which not only meets the legal requirements, but also provides comfort of using of buildings, requires knowledge of the materials and solutions. Since moisture is one of the main factors that can affect the building structure destruction, it is particularly important to be aware of hygrothermal properties of components. And this is the focus of the study. In this paper several variants of external walls were analysed, according to the requirements in terms of: heat transfer coefficient U, the risk of surface and interstitial condensation. Partitions were designed with composite based on shives from industrial hemp and lime binder, which is not yet widely used in Poland. The purpose of the analysis of this material was to prove the validity of using the natural materials in residential buildings.